Using the regression statistic method to analyses the relation between ASPT and chemical index - Ha, Le Thu (Academia Journal of Biology, 2015)
Data for ASPT, DO, BOD5 and COD values were obtained for fourteen stations during the years 1998, 1999, 2000 and 2001. Samples were taken in March, June, September and December from four catchments: Tamdao stream, Vucthuyen river, Cauton river and Calo river. The Tools-Data Analysis-Regression computer program of Microsoft Excel was used to analyse the relation between ASPT and chemical index. The multiple-regression analysis indicated that ASPT was closely related to chemical index. These relationships were significant with P value lower than 0.05, and this analysis also indicated that ASPT was best closely related to DO (dissolved oxygen) and COD.